How FDI in the mining sector can assist communities to achieve sustainable development - James Otto (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
Governments increasingly mandate that mining companies implement sustainable development initiatives in communities affected by their operations. The use of corporate social responsibility programs and community development agreements can help communities to overcome the historical boom-bust cycle associated with large mines and broaden their ability to prosper after the mine closes.
Keywords: 330